2013
DOI: 10.1016/j.ajodo.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional changes of upper airway after rapid maxillary expansion: A prospective cone-beam computed tomography study

Abstract: These results confirm the findings of previous studies of the effect of rapid maxillary expansion on the maxilla. Additionally, we found that only the cross-sectional area of the upper airway at the posterior nasal spine to basion level significantly gains a moderate increase after rapid maxillary expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 25 publications
6
92
1
14
Order By: Relevance
“…From their data, the authors agreed with previous studies that RPE indeed may cause significant expansion of the maxilla. Furthermore, they concluded that there is a significant increase in the cross-sectional area of the upper airway following rapid maxillary expansion [16]. Therefore, recent CBCT studies show agreement with earlier hard tissue studies on expansion effects.…”
Section: Skeletal Effects Of Palatal Expansionsupporting
confidence: 74%
“…From their data, the authors agreed with previous studies that RPE indeed may cause significant expansion of the maxilla. Furthermore, they concluded that there is a significant increase in the cross-sectional area of the upper airway following rapid maxillary expansion [16]. Therefore, recent CBCT studies show agreement with earlier hard tissue studies on expansion effects.…”
Section: Skeletal Effects Of Palatal Expansionsupporting
confidence: 74%
“…While the effect of expansion was not accounted for in the present study, it may not have a significant influence. Several studies have used CBCT scans to evaluate airway changes following palatal expansion, finding no statistically significant effect on OA volume, [30][31][32][33][34] although significant effects have been demonstrated in the nasopharyngeal airway. 35 Lastly, CBCT scans were obtained in the current study with subjects in a seated position.…”
Section: Discussionmentioning
confidence: 99%
“…Além da nasofaringe, outros pesquisadores relataram também o efeito da ERM sobre a orofaringe (El;Palomo, 2010;Zhao et al, 2010;Ribeiro et al, 2012;Smith et al, 2012;Izuka;Feres;Pignatari, 2015) Figura 6 -Alteração da baixa postura da língua e aumento da via aérea faríngea após ERM em um paciente: (A) antes da ERM, a postura da língua é baixa (seta vermelha) e a via aérea orofaríngea é estreita; (B) após ERM, a postura da língua melhorou (seta amarela) e a via aérea da faringe aumentou (setas azuis) Chang et al (2013) …”
Section: Expansão Rápida Da Maxila E Efeitos Na Nasofaringe E Orofaringeunclassified
“…Smith et al (2012 No que se refere às constrições das vias aéreas orofaríngeas, estas têm sido responsáveis por desempenharem papel significativo na fisiopatologia da apneia obstrutiva do sono (Johal et al, 2007); devido à associação com postura mais baixa da língua, característica comum nos pacientes com atresia maxilar (Linder-Aronson, 1970). No entanto, poucos estudos avaliaram o impacto da expansão maxilar na orofaringe (El;Palomo, 2014;Zhao et al, 2010;Ribeiro et al, 2012;Smith et al, 2012, Pangrazio-Kulbersh et al, 2012, Chang et al, 2013Izuka;Feres;Pignatari, 2015). Apenas Ribeiro et al (2012) encontraram alterações significativas nas dimensões dessa região ao avaliarem 15 pacientes com 7,5 anos de idade, em média, portadores de deficiência na largura maxilar, tratados com aparelho dento-suportado, similar ao proposto por Cohen e Silverman (1973).…”
Section: Figura 11 -Média (Ic 95%) Volume Vs Região E Gruposunclassified
See 1 more Smart Citation